Chronic thromboembolic pulmonary hypertension and impairment after pulmonary embolism: the FOCUS study . (29th April 2022) - Valerio, Luca; Mavromanoli, Anna C; Barco, Stefano; Abele, Christina; Becker, Dorothea; Bruch, Leonhard; Ewert, Ralf; Faehling, Martin; Fistera, David; Gerhardt, Felix; Ghofrani, Hossein Ardeschir; Grgic, Aleksandar; et al.
Abstract: Aims: To systematically assess late outcomes of acute pulmonary embolism (PE) and to investigate the clinical implications of post-PE impairment (PPEI) fulfilling prospectively defined criteria. Methods and results: A prospective multicentre observational cohort study was conducted in 17 large-volume centres across Germany. Adult consecutive patients with confirmed acute symptomatic PE were followed with a standardized assessment plan and pre-defined visits at 3, 12, and 24 months. The co-primary outcomes were (i) diagnosis of chronic thromboembolic pulmonary hypertension (CTEPH), and (ii) PPEI, a combination of persistent or worsening clinical, functional, biochemical, and imaging parameters during follow-up. A total of 1017 patients (45% women, median age 64 years) were included in the primary analysis. They were followed for a median duration of 732 days after PE diagnosis. The CTEPH was diagnosed in 16 (1.6%) patients, after a median of 129 days; the estimated 2-year cumulative incidence was 2.3% (1.2–4.4%). Overall, 880 patients were evaluable for PPEI; the 2-year cumulative incidence was 16.0% (95% confidence interval 12.8–20.8%). The PPEI helped to identify 15 of the 16 patients diagnosed with CTEPH during follow-up (hazard ratio for CTEPH vs. no CTEPH 393; 95% confidence interval 73–2119). Patients with PPEI had a higher risk of re-hospitalization and death as well as worse quality of life compared with those without PPEI. Conclusion: In this prospective study, the cumulative 2-year incidence of CTEPH was 2.3%, but PPEI diagnosed by standardized criteria was frequent. Our findings support systematic follow-up of patients after acute PE and may help to optimize guideline recommendations and algorithms for post-PE care. Structured Graphical Abstract: Structured Graphical Abstract Design and main results of the FOllow-up after aCUte pulmonary emboliSm (FOCUS) study. BNP, brain natriuretic peptide; CTEPH, chronic thromboembolic pulmonary hypertension; LV, left ventricular; NT-proBNP, N-terminal probrain natriuretic peptide; PE, pulmonary embolism; PPEI, post-pulmonary embolism impairment; RA, right atrial; RV, right ventricular; TAPSE, tricuspid annular plane systolic excursion; WHO, World Health Organization.